(untitled) (Journal of Innovative Solutions for Eco-Environmental Sustainability, 2025)
Chronic exposure to multiple foodborne mycotoxins poses a significant health risk, yet the nuclear and nucleolar morphological responses of hepatocytes remain insufficiently characterized. This study investigated the cytomorphometric changes in hepatocyte nuclei and nucleoli of rats administered a combination of three common mycotoxins: aflatoxin B1, ochratoxin A, and zearalenone. Experimental animals were divided into three groups receiving daily contaminated feed for 15, 30, or 60 days. Cytological preparations from liver tissues were analyzed using DNA cytophotometry and morphometric methods to quantify nuclear and nucleolar DNA content and area. Results showed that by day 15, the nuclear and nucleolar area and DNA content had significantly increased compared to controls (p<0.01), suggesting enhanced transcriptional activity. This trend continued with reduced intensity by day 30. At day 60, while nuclear size and DNA content slightly decreased, nucleolar indices remained elevated, indicating sustained transcriptional activation. The frequency of mononucleolar and binucleolar hepatocytes increased, along with occasional trinucleolar cells (1–2%). Ploidy analysis revealed the presence of subdiploid nuclei by day 30, representing 25% of hepatocytes, whereas by day 60, the ploidy profile approached control values, implying a partial restoration. These data indicate that dietary exposure to aflatoxin B1, ochratoxin A, and zearalenone induces early nuclear hypertrophy and nucleolar activation in hepatocytes, followed by potential adaptive responses over time. Understanding such adaptive plasticity may offer insights into hepatocellular resilience under toxic stress.